Massive Sequencing of V3-V4 Hypervariable Region in Pyogenic Liver Abscesses Reveals the Presence of Unusual Bacteria Not Detected by Classical Culture Methods - Verónica Fernández-Sánchez; Estibeyesbo Said Plascencia-Nieto; Mónica Alethia Cureño-Díaz; Emilio Mariano Durán-Manuel; Aida Verónica Rodríguez-Tovar; Claudia Camelia Calzada-Mendoza; Clemente Cruz-Cruz; Miguel Ángel Loyola-Cruz; María Elizbeth Álvarez-Sánchez; Juan Carlos Bravata-Alcántara; Enzo Vásquez-Jiménez; Víctor Hugo Gutiérrez-Muñoz; et al. (Microorganisms)
Pyogenic liver abscesses (PLAs) are serious infections in which doctors often fail in identifying the causative agent due to microbiological limitations. These limitations in detecting uncommon pathogens complicate the treatment and recovery. Molecular techniques, like massive sequencing, enable the detection of uncommon pathogens and highlight the shortcomings of traditional cultures. The aim of this work was to characterise the bacterial composition of PLAs through massive sequencing of the V3-V4 hypervariable region of the 16S rRNA gene in cases where conventional culture methods were negative. Purulent material was collected from three patients with PLAs at Hospital Juárez de México. Classical and molecular microbiological cultures were performed in parallel. Metagenomic DNA was extracted and massively sequenced (16S rRNA gene) using the Illumina MiSeq platform. A bioinformatic analysis was performed to determine the diversity at six different taxa levels and the relative abundances. The culture methods were not sufficient to detect the causative agent of the PLAs. However, the massive sequencing revealed the causative agents of the monomicrobial and polymicrobial infectious foci, with Gardnerella vaginalis, Lactobacillus iners, and Prevotella timonensis as the dominant bacteria. The massive sequencing revealed the presence of unusual pathogens that traditional culture failed to detect. There is an immediate need for molecular or comprehensive microbiological culture techniques to search for unusual bacteria in the diagnosis of PLAs.